Enrichment of Organic-Inorganic Se and Vitamin E in Quail Products and Their Effects on Performances and Antioxidant Source in Quail Eggs - Syahrir Akil; Wiranda Gentini Piliang (Cutting-edge Research in Agricultural Sciences Vol. 10, 2021)
The purpose of this study was to find the optimal level of combined organic selenium, inorganic selenium, and vitamin E for optimal quail production and reproduction, as well as the highest antioxidant level in quail eggs. In this study, seven hundred twenty quails (360 females and 360 males) were used at the age of six weeks. There were nine different treatment diets: To (commercial diet/control), T1 (diet containing 0.46 ppm inorganic Se + 43.50 ppm vitamin E), T2 (diet containing 0.46 ppm inorganic Se + 87.00 ppm vitamin E), T3 (diet containing 0.92 ppm inorganic Se + 43.50 ppm vitamin E), T4 (diet containing 0.92 ppm inorganic Se +87.00 ppm vitamin E), T5 (diet containing 0.46 ppm organic Se + 43.50 ppm vitamin E), T6 (diet containing 0.46 ppm organic Se + 87.00 ppm vitamin E), T7 (diet containing 0.92 ppm organic Se + 43.50 vitamin E) and T8 (diet containing 0.92 ppm organic Se 0.92 +87.00 ppm vitamin E). The experiment was set up in a factorial nested design. Duncan’s test was used to look for any significant changes between the treatments. According to the findings of this study, 0.92 ppm organic selenium + 43.50 ppm vitamin E (T7) in general provided the highest selenium content in meat, egg albumin, and egg yolk, as well as hatchability. The antioxidants represented by vitamin E and glutathione peroxidase enzyme in quail eggs were significantly higher than in quails fed other treatment diets.